Stress Among Caregivers of Cancer Patients: An Integrated Review (International Journal of Psychiatric Nursing, 2025)
Background: Caregivers of cancer patients often experience significant stress, impacting their mental and physical health. Understanding the factors contributing to this stress is crucial for developing effective support interventions.Objective: This integrated review aims to synthesize existing literature on stress among caregivers of cancer patients, identifying key stressors, coping mechanisms, and outcomes.Methods: Following PRISMA guidelines, a comprehensive search was conducted across databases including PubMed, PsycINFO, and CINAHL for studies published between 2010 and 2024. Inclusion criteria encompassed quantitative, qualitative, and mixed-methods studies focusing on caregiver stress in the context of cancer care.Results: A total of 15 studies met the inclusion criteria. Major stressors identified include emotional burden, financial strain, time constraints, and lack of social support. Coping mechanisms varied, with adaptive strategies such as problem-solving and seeking social support being common, while maladaptive strategies included avoidance and substance use. Outcomes of caregiver stress were associated with decreased quality of life, mental health issues like depression and anxiety, and adverse physical health effects.Conclusion: Caregiver stress in cancer care is multifaceted, necessitating comprehensive support systems. Interventions should target both the reduction of stressors and the enhancement of effective coping strategies to improve caregiver well-being.
Keywords: caregiver stress; cancer patient; cancer care; integrated review; coping mechanisms